THE PROBLEMS OF PROTOTYPE MODELS IN COGNITIVE LINGUISTICS (Conferencea, 2022)
This article reflects on the realizing and use of prototype theory of notion in cognitive linguistics. Generally, prototype focuses on the comprehending and misunderstanding by the linguistic scholars, its initial use and extended use in the field. To assess prototype’s life and role in cognitive linguistics a number of cognitive psychologists mainly Rosch, Cohen,Murphy,Daniel Aberra, Komatsu, Geeraerts‘ scientific works have been studied. As a result, It is observed that: There are some misunderstandings of prototype‘s main tenets and confusing them with other types of the theory of concepts. In this article, some theoretical notions and practical examples to the prototype are given. For instance, unlike other prototype models, there given a new prototypical sample such as reptiles that it is based on their lives, forms and organic structure of reptiles. They have been analyzed by prototypical categorization below.